Food Systems Resilience - Ribeiro-Barros, Ana I.; Tevera, Daniel S.; Goulao, Luís F.; Tivana, Lucas D. (Sustainable Development, 2022)
This book addresses some of the major challenges of food systems associated with a diversity of agricultural contexts and priorities. It contributes to the conversation on global food and nutrition security by unpacking the intertwined connections between food system resilience, food policies, and global food markets. The contributing authors provide careful analyses of how shocks to food systems (e.g., COVID-19 pandemic lockdowns) and crises to global food systems (e.g., the global food price crisis of 2008) have disrupted the food value chains in ways that undermine global initiatives to achieve food and nutrition security for all. The book is divided into two sections. Section 1 focuses on global food systems transformation with the goal of moving towards resilience. Two chapters in this section employ a global context approach to address the key factors undermining food systems' resilience and sustainability. Section 2 presents case studies drawn from Africa, Asia, and Europe with different pathways for the transition to food systems resilience, highlighting the importance of policy approaches as well as smart and innovative strategies to ensure the production of nutritious foods at affordable costs, the reduction of food wastage, and the valorization of sub-products.